2000
DOI: 10.1002/1096-9896(2000)9999:9999<::aid-path761>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Specific patterns of chromosomal abnormalities are associated with RER status in sporadic colorectal cancer

Abstract: Current opinion of the genetic events driving colorectal tumourigenesis focuses on genomic instability. At least two apparently independent mechanisms are recognized, microsatellite instability and chromosomal instability. The genetic defects underlying each type of instability are only partially understood and controversy remains as to the role of p53 in the generation of chromosomal defects in colorectal cancer. This study sought to clarify the relationships between chromosomal abnormalities and defects of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The majority of previous studies about CIs in MSI-H tumors have included a small number of cases, and the results obtained have been conflicting. 11,12,[27][28][29] The co-existence of two kinds of genomic instability in several colorectal cancer cell lines has been reported. 13 In this study, we examined CIs in a relatively large number of cases (n ϭ 39) and found CIs in 12 (31%) cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of previous studies about CIs in MSI-H tumors have included a small number of cases, and the results obtained have been conflicting. 11,12,[27][28][29] The co-existence of two kinds of genomic instability in several colorectal cancer cell lines has been reported. 13 In this study, we examined CIs in a relatively large number of cases (n ϭ 39) and found CIs in 12 (31%) cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although these two distinct major genetic pathways of genetic instabilities are widely accepted, some tumors reveal different genetic pathways; ie, some tumors show both types of genomic instabilities and some tumors do not show any of these two instabilities. [11][12][13] To clarify the relationship between these two genetic instabilities in colorectal carcinomas, we analyzed chromosomal imbalances (CIs) in 39 MSI-H colorectal carcinomas and compared the results with changes in 20 microsatellite-stable (MSS) colorectal carcinomas.…”
mentioning
confidence: 99%
“…Microsatellite instability is a well-known form of genome instability caused by a defective mismatch repair system, with tumor cells being unable to keep a constant length of repetitive microsatellite sequences scattered throughout the genome [7]. MSI tumors are known to have a near-diploid karyotype [811]. On the other hand, among microsatellite-stable (MSS) tumors, two groups can be distinguished according to the amount of chromosomal aberrations: tumors with low numbers of BCNAs and tumors with high numbers of BCNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1993 a discrete group of sporadic colorectal cancer that displays microsatellite instability (MSI-H) throughout tumour DNA, arising as a result of mismatch repair (MMR) deficiency, has also been recognized [2][3][4]. More recently, a further subset of colorectal cancer characterized by an absence of both MSI-H and chromosome instability has been described [5][6][7]. Further studies have confirmed the existence of this subset and they have been described as microsatellite and chromosome stable (MACS) cancers because of their diploid DNA content and lack of MMR deficiency.…”
Section: Introductionmentioning
confidence: 99%